Analysis of cells obtained by bronchial lavage of infants with respiratory syncytial virus infection. Issue 5 (November 1994) - Everard, M L; Swarbrick, A; Wrightham, M; McIntyre, J; Dunkley, C; James, P D; Sewell, H F; Milner, A D
Abstract : To study the cellular infiltrate that occurs within the airways of infants with respiratory syncytial virus bronchiolitis, samples of airways secretions were obtained by bronchial lavage from the lower respiratory tract of infants ventilated for this condition and from the upper airway of non-intubated infants with this disorder using nasopharyngeal aspirates. Cytospin samples were prepared so that differential cell counts could be performed on the cells obtained and alkaline phosphatase-antialkaline phosphatase immunocytochemical analysis of lymphocyte subsets was carried out using a panel of monoclonal antibodies, which included anti-CD3, anti-CD4, anti-CD8, anti-CD19, and anti-TcR gamma delta. Results from the lower and upper airways were similar. Large numbers of inflammatory cells were obtained, of which neutrophils accounted for a median of 93% in the upper airway and 76% in the lower airway. The numbers of CD8 positive cells detected were small and consistently less than CD4 positive cells, median CD4:CD8 ratios being 22.5:1 and 15:1 for the lower and upper airways. CD19 positive cells were rarely observed and no gamma delta positive lymphocytes were detected. These results indicate that neutrophils probably play a major part in causing symptoms in these infants. They do not support the concept that excessive lymphocyte mediated cytotoxic activity is principally responsible for the pathology in respiratory syncytial virus bronchiolitis.